(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: To evaluate the outcomes of Lichtenstein tension-free hernioplasty in the treatment of inguinal hernia at Ha Tinh General Hospital in 2025. Patients and Methods: A prospective descriptive study was conducted on 32 male patients diagnosed with inguinal hernia who underwent Lichtenstein repair from January 2025 to December 2025. Results: The mean age was 58,6 years (range: 25–82), with 43,8% of patients aged over 60. Right-sided inguinal hernia accounted for 56.3%, while bilateral hernia was observed in 9,3%. The mean operative time was 64,8 ± 18,5 minutes, with indirect hernia identified in 40,0% of cases intraoperatively. Most patients (75,0%) were able to ambulate within 24 hours postoperatively. The mean duration of postoperative pain was 4,5 days. The rate of early complications was 12,5%, and the mean hospital stay was 6,1 ± 1,7 days. With a mean follow-up period of 3,6 months, one case of chronic groin pain was recorded, and no recurrence was observed. Conclusion: Lichtenstein hernioplasty is a safe and effective method for the treatment of inguinal hernia, with a low complication rate and during the follow-up period, no recurrence was documented.